Formação e atuação profissional: Uma relação indissociável - Menezes, Vanessa Bega (2006)
The present thesis focuses on two basic dimensions of the profession of Social Work: educational formation and professional practice, from the perspective of the guidelines established by the ethical and political project developed by this professional category during the decades of 1980 and 1990. In terms of formation, it considers the need for continued education, while political, civic and professional participation is viewed in the context of professional practice. Both are regarded as potentially contributing to a professional practice embedded in that project. The discussion is guided by Critical Theory for the analysis of social reality and, therefore, its fundamental arguments deal with the challenges faced by the profession to articulate both dimensions in the present conjuncture. Thus, the thesis aims to contribute to the appropriation of such a professional, ethical and political project by reflecting on the need to materialize its principles